Nursing institutions' professors' perception and distant education experience during COVID-19 pandemic lockdown - Anis Sfendla; Abdelilah Merabti; Salwa Lahjou; Nisrin El Mlili; Hind Bahri; Banacer Himmi; Abdelhakim El Ouali Lalami (Wolters Kluwer Medknow Publications, 2024)
Background: The nursing profession represents a demanding and challenging profession with a purpose to keep up with the evolving health-care demands of the population. Aims: The purpose of this study is to assess nursing institutions' professors' previous experience about information and communication technologies (ICTs) and their perception of distant education during the pandemic lockdown. Materials and Methods: This present is a cross-sectional study among participants n = 249 recruited from all academic staff (N = 694) of 23 higher institutes of nursing professions and health techniques in Morocco. The Chi-square test for independence (χ2) and adjusted Z scores were used as a data analysis method to assess the association between the professors' education levels and ICT experience. Results: A significant association [χ2 (1, n = 249) = 19.510, P < 0.001] was revealed between professors' education level and taken training related to ICT in education; significant few professors (16; 9.3%) reported that taken training session [χ2 (1, n = 249) = 8.940, P = 0.003] belonged to the bachelor degree group. In matters of perception, a few proportion (10%) reported that using technology effectively belonged to the bachelor and low education background group. Conclusions: The findings showed that having previous experience in teaching remotely and training related to the ICT was significantly associated with a higher education background. Moreover, professors with higher degrees agreed that distant education could be an alternative to face-to-face course during quarantine.